The Clinical Application of 3D-Printed Boluses in Superficial Tumor Radiotherapy - Wang, Xiran; Wang, Xuetao; Xiang, Zhongzheng; Zeng, Yuanyuan; Liu, Fang; Shao, Bianfei; He, Tao; Ma, Jiachun; Yu, Siting; Liu, Lei (Frontiers in Oncology, 2021)
During the procedure of radiotherapy for superficial tumors, the key to treatment is to ensure that the skin surface receives an adequate radiation dose prescribed. However, due to the presence of the built-up effect of high-energy rays, bolus with appropriate thickness should be placed on the skin surface to increase the target radiation dose. Traditional bolus like wet gauze usually do not fit the skin perfectly, resulting in air gaps between the skin and the bolus, as these unwanted but avoidable air gaps leading to a decrease of the radiation dose in the target area and poor effect of radiotherapy. Three-dimensional printing, a new rising technology named “additive manufacturing” (AM), could create physical models with specific shapes from digital information by using special materials. It has been favored in many fields because of its advantages, including less waste, low-cost and individualized design. It is not an exception in the field of radiotherapy, personalized bolus made through three-dimensional printing technology also make up for numbers of shortcomings of the traditional commercial bolus. Therefore, increasing number of researchers have tried to use three-dimensional printed bolus for clinical applications rather than commercial bolus. Here, we review the three-dimensional printed bolus’s material selection and production process, its clinical applications and potential radioactive dermatitis. At last, we discuss some challenges still need to face and future prospects of three-dimensional printed bolus.